Hyperbilirubinemia after cardiac surgery: An observational study. (November 2015) - Sharma, Pranav; Ananthanarayanan, Chandrasekaran; Vaidhya, Nikunj; Malhotra, Amber; Shah, Komal; Sharma, Ramanand
Background: We aimed to assess the incidence and perioperative risk factors for hyperbilirubinemia after cardiac surgery, and determine its influence on early operative outcome. Methods: This prospective observational study was conducted on 476 patients who underwent cardiac surgical procedures from January 2014 to March 2014. Postoperative hyperbilirubinemia was defined as serum total bilirubin >2.0 mg dL −1 . Results: The overall incidence of postoperative hyperbilirubinemia was 25% (119 patients). Patients undergoing valve repair or replacement had the highest incidence of hyperbilirubinemia (36.2%), followed by coronary artery bypass grafting with concomitant valve surgery (34.1%), congenital heart surgery (23.1%), and coronary artery bypass alone (12.7%). Postoperative hyperbilirubinemia was associated with increased duration of inotropic support ( p  = 0.0001), mechanical ventilation ( p  = 0.0001), intensive care unit stay ( p  = 0.001), hospital stay ( p  = 0.006), and mortality ( p  = 0.014). The perioperative factors associated with postoperative hyperbilirubinemia were increased preoperative bilirubin level ( p  < 0.0001), preoperative prothrombin time ( p  < 0.0001), cardiopulmonary bypass time ( p  = 0.028), aortic crossclamp time ( p  = 0.004), and blood transfusion units ( p  = 0.0001). Conclusions: Postoperative hyperbilirubinemia is common in patients undergoing cardiopulmonary bypass and is associated with high hospital mortality. The factors associated with its occurrence are increased preoperative bilirubin level, preoperative prothrombin time, cardiopulmonary bypass time, aortic crossclamp time, and blood transfusion units. Persistent hyperbilirubinemia is associated with a worse outcome than early transient hyperbilirubinemia.